Remoção do corante Solophenyl preto utilizando floculação iônica - Lima, Larícia Nogueira de (Universidade Federal Rural do Semi-Árido, 2018)
The textile industry is considerate one the most pollutants in industrial area, in which your main cause is the contamination water with organic compounds, where the most these substances are harmful for the environment. Faced with this, it is observed the necessity do the water treatment before discard, therefore, this work propose the use the ionic flocculation for the treatment of textiles effluents, being the model polluting was the black solophenyl. Ionic flocculation consists of the process of mixing the tensoactive, because this one is much utilized in separation process, together with the model polluting and the addition of zinc on solution, when they react, result in the formation of insoluble tensoactive, where the same will attract the molecules of the black solophenyl through adsorption. In this work, the ionic flocculation is analyzed through of tensoactive concentration, pH and the use of electrolytes. Noting that in both processes there was removal of the pollutant model of more than 90%, in which the best result was with pH 10, where it removed 97% of dye, thus concluding, that in fact the ionic flocculation technique is quite efficient in the process of treatment of textile effluents.
Keywords: Tensoativo; Corante; Floculação iônica; Efluentes têxteis; Tensoactive; Dye; Ionic flocculation; Textile effluents; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA